2010
DOI: 10.1002/jmri.22154
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the elbow

Abstract: Elbow pain is frequently encountered in clinical practice and can result in significant morbidity, particularly in athletes. Magnetic resonance imaging (MRI) is an excellent diagnostic imaging tool for the evaluation of soft tissue and osteochondral pathology around the elbow. Recent advances in magnetic field strength and coil design have lead to improved spatial resolution and superior soft tissue contrast, making it ideal for visualization of complex joint anatomy. This article describes the normal imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 102 publications
0
9
1
Order By: Relevance
“…18 The more recent use of gradient-echo sequences, in combination with short tau inversion recovery sequence (for fat suppression) may be better in evaluating articular cartilage and to better delineate loose bodies in the elbow joint; it may also be that 3T MRI will improve the accuracy of the diagnosis of articular cartilage defect compared with the 1.5 T MRI technology used in this study, although this has yet to be demonstrated. 7,[19][20][21] In our series of 31 patients, in comparison with MRI, the use of MRA did not increase the diagnostic accuracy of detecting chondral lesions of any of the 4 anatomical lesions. This is in contrast to the known effects of MRA in enhancing visualization of capsular abnormalities, undersurface collateral ligament tears, OCD, and intraarticular loose bodies.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…18 The more recent use of gradient-echo sequences, in combination with short tau inversion recovery sequence (for fat suppression) may be better in evaluating articular cartilage and to better delineate loose bodies in the elbow joint; it may also be that 3T MRI will improve the accuracy of the diagnosis of articular cartilage defect compared with the 1.5 T MRI technology used in this study, although this has yet to be demonstrated. 7,[19][20][21] In our series of 31 patients, in comparison with MRI, the use of MRA did not increase the diagnostic accuracy of detecting chondral lesions of any of the 4 anatomical lesions. This is in contrast to the known effects of MRA in enhancing visualization of capsular abnormalities, undersurface collateral ligament tears, OCD, and intraarticular loose bodies.…”
Section: Discussioncontrasting
confidence: 45%
“…4,5 However, MRI does have some limitations in diagnosing elbow pathology, related to positioning difficulty, scarcity of dedicated elbow coils, and lower signal-to-noise ratio at the magnet. 6,7 The literature contains reports using MRI and MRA to detect articular surface lesions in the knee and the shoulder. [8][9][10][11] However, there are no studies assessing the sensitivity, specificity, and accuracy of MRI in detecting isolated chondral lesions of the elbow.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2), subchondral sclerosis, separated and/or displaced bony fragments, in addition to effusion in the acute setting. 19,20 The radiographic stages of OCD are the radiolucent stage, separation stage, and free (advanced) stage (►Table 2). 21 Negative radiographs do not exclude an osteochondral lesion, and Kijowski and colleagues reported a 66% sensitivity of radiographs in the detection of capitellar OCD and only a 57% detection rate of intra-articular bodies when compared with arthroscopic findings.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…Prior to discussing actual osteochondral injuries of the elbow, normal locations in the elbow that lack cartilage and are observable on MRI should be mentioned: the pseudodefects of the trochlea and the capitellum. 11,19,20,[28][29][30] Because only anterior 180 degrees of the capitellum is covered by articular coverage, the posterior bare area contributes to the pseudodefect of the capitellum (►Fig. 5a).…”
Section: Computed Tomography and Computed Tomography Arthrographymentioning
confidence: 99%
See 1 more Smart Citation